1991
DOI: 10.1002/1097-0142(19911101)68:9<1918::aid-cncr2820680913>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of internal mammary node metastases as a prognostic factor in patients with breast cancer

Abstract: Clinical, histologic, and biologic prognostic factors were examined in 144 patients with invasive breast cancer. It was determined whether variable prognostic factors, especially internal mammary lymph node metastases, would serve as a basis for the prognosis of breast cancer. In a univariate study, overall survival was significantly correlated with tumor size, axillary lymph node status, axillary and internal mammary lymph node metastases, and DNA ploidy status. Especially among patients with one to three pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 34 publications
1
15
0
3
Order By: Relevance
“…The status of axillary and internal mammary lymph nodes (IMN) is one of the most signi cant prognostic factors for survival in breast cancer (1)(2)(3)(4). The reappraisal of internal mammary node metastases as a prognostic factor and the results of recent publications of trials of postmastectomy irradiation have aroused discussion about adopting routine elective IMN irradiation despite potential serious cardiac morbidity (4)(5)(6).…”
mentioning
confidence: 99%
“…The status of axillary and internal mammary lymph nodes (IMN) is one of the most signi cant prognostic factors for survival in breast cancer (1)(2)(3)(4). The reappraisal of internal mammary node metastases as a prognostic factor and the results of recent publications of trials of postmastectomy irradiation have aroused discussion about adopting routine elective IMN irradiation despite potential serious cardiac morbidity (4)(5)(6).…”
mentioning
confidence: 99%
“…Also, the tumors located medially have high rates of failure because they are related to the lymphatic drainage to the internal mammary lymph nodes and the SLNB of these nodes are not performed. The internal mammary lymph nodes have the same prognostic significance as axillary nodal metastasis [18,19] . O'Hea et al reported that the accuracy of SLNB decreases with the increasing tumor size [20] .…”
Section: Discussionmentioning
confidence: 99%
“…[298][299][300] Isolated internal mammary nodal metastases carry the same prognostic implications as isolated axillary nodal metastases. 301,302 If the identification of such metastases would alter therapeutic management, then the determination by lymphoscintigraphy of those few patients with internal mammary drainage patterns, and sentinel lymphadenectomy of those nodes, would be justified. The presence of both internal mammary and axillary drainage has significant adverse prognostic significance, but because most patients with internal mammary drainage also have axillary drainage, an effort to map internal mammary sentinel nodes has the potential to benefit only a small number of patients.…”
Section: Is Internal Mammary Sentinel Lymphadenectomy Indicated?mentioning
confidence: 98%